A Brain Signature to Differentiate Acute and Chronic Pain in Rats - Guo, Yifei; Wang, Yuzheng; Sun, Yabin; Wang, Jin-Yan (Frontiers in Computational Neuroscience, 2016)
The transition from acute pain to chronic pain entails considerable changes of patients at multiple levels of the nervous system and in psychological states. An accurate differentiation between acute and chronic pain is essential in pain management as it may help optimize analgesic treatments according to the pain state of patients. Given that acute and chronic pain could modulate brain states in different ways and that brain states could greatly shape the neural processing of external inputs, we hypothesized that acute and chronic pain would show differential effects on cortical responses to non-nociceptive sensory information. Here, by analyzing auditory-evoked potentials (AEPs) to pure tones in rats with acute or chronic pain, we found opposite influences of acute and chronic pain on cortical responses to auditory inputs. In particular, compared to no-pain controls, the N100 wave of rat AEPs was significantly enhanced in rats with acute pain but significantly reduced in rats with chronic pain, indicating that acute pain facilitated cortical processing of auditory information while chronic pain exerted an inhibitory effect. These findings could be justified by the fact that individuals suffering from acute or chronic pain would have different vigilance states, i.e., the vigilance level to external sensory stimuli would be increased with acute pain, but decreased with chronic pain. Therefore, this auditory response holds promise of being a brain signature to differentiate acute and chronic pain. Instead of investigating the pain system per se, the study of pain-induced influences on cortical processing of non-nocicpetive sensory information might represent a potential strategy to monitor the progress of pain chronification in clinical applications.